Method for measuring and calculating particle size and inorganic coating thickness of titanium dioxide finished product
Patent Information
- Application Number
- CN202410078123.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-01-19
AI Technical Summary
钛白粉成品的粒径主要包含钛白粉粒子本身的粒径和无机包膜的厚度,对于钛白粉本身的粒径控制可以通过粒径测试仪进行测试,对于无机包膜厚度的测试,目前主要是根据包膜层的透射度及与钛白粉的明显边界,通过透射电镜(TEM)的方法,来量出钛白粉的无机包膜厚度,但由于透射电镜的造价和维护费用较高,故大多数企业没有透射电镜,仅凭经验进行包膜,通过成品粒径的测试来评判钛白粉的最终粒径,但是该方法易受汽粉粉碎强度和测试方法的影响,往往测试的是多个团聚体的粒径或者汽粉、测试时过度研磨造成无机包膜膜层的脱落,造成产品粒径测试不准确
[0026]This invention assumes that the inorganic coating material and titanium dioxide molecules are spherical, and that the inorganic coating material is uniformly coated onto the titanium dioxide particles. Then, by testing the particle size and density of the titanium dioxide particles before and after sand milling, the coating mass percentage of different inorganic coating materials in the finished product, the ratio of the molar molecular mass of the corresponding hydroxides or hydrates to oxides of different inorganic coating materials, and the density of the hydroxides or hydrates of different inorganic coating materials (or oxides if there are no hydroxides or hydrates), the inorganic coating thickness of the finished titanium dioxide products with different inorganic coatings can be calculated. This testing method avoids the problem of inaccurate particle size of coated titanium dioxide or finished product caused by agglomeration of titanium dioxide. It uses the volume of titanium dioxide obtained from the particle size of uncoated titanium dioxide after sand milling and the volume of coating material obtained through precise calculation, so as to accurately calculate the particle size of coated titanium dioxide, and then accurately calculate the coating thickness of titanium dioxide. The testing or calculation process is relatively simple, with a small amount of computation, and the data accuracy has been verified to be high. Compared with transmission electron microscopy, the calculation cost is lower and it is more suitable for titanium dioxide companies.
Smart Images

Figure CN117890271B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials analysis and testing technology, and specifically relates to a method for calculating the particle size and inorganic coating thickness of finished titanium dioxide. Background Technology
[0002] Titanium dioxide, with the chemical formula TiO2, is an important inorganic chemical pigment widely used in coatings, plastics, inks, and papermaking. The main factors affecting the performance of titanium dioxide include its whiteness, particle size, particle size distribution, rutile conversion rate, and inorganic and organic surface treatments. Among these, particle size is a major factor. In low-content titanium dioxide systems, larger particle sizes result in less effective light reflection due to the gap effect of large particles, leading to poorer hiding power compared to smaller particles. Conversely, in high-content titanium dioxide systems, smaller particle sizes result in less effective pigment performance due to the congestion effect of small particles, resulting in poorer hiding power compared to larger particles.
[0003] The process from titanium dioxide raw material (such as sulfuric acid process kiln-fired products) to finished titanium dioxide generally involves wet milling, sand milling, inorganic coating, water washing, flash drying, and steam pulverization. The particle size of the finished titanium dioxide mainly includes the particle size of the titanium dioxide particles themselves and the thickness of the inorganic coating. The particle size of the titanium dioxide itself can be controlled by a particle size analyzer. For the measurement of the inorganic coating thickness, it is currently mainly based on the transmittance of the coating layer and the clear boundary between the coating layer and the titanium dioxide, using transmission electron microscopy (TEM) to measure the thickness of the inorganic coating. However, due to the high cost and maintenance of TEM, most companies do not have TEM and rely solely on experience for coating, judging the final particle size of titanium dioxide by measuring the particle size of the finished product. However, this method is easily affected by the intensity of steam pulverization and the testing method, often measuring the particle size of multiple agglomerates or steam pulverization. Excessive grinding during testing can cause the inorganic coating layer to peel off, resulting in inaccurate particle size measurements. Some methods infer coating thickness by testing the particle size of coated titanium dioxide. However, during coating deposition, titanium dioxide agglomerates, and some coating agents may nucleate independently or adhere to the titanium dioxide coating surface, leading to inaccurate particle size measurements. Furthermore, appropriate air powder treatment can polish and reorganize the coating layer, enhancing its pigment properties. Neither the finished particle size nor the coated particle size can accurately measure the coating thickness of titanium dioxide, failing to reflect its true performance in various application systems. Therefore, there is an urgent need to develop a simple method for calculating the inorganic coating thickness of titanium dioxide, providing theoretical support for practical applications. Simultaneously, calculating the accurate particle size of coated titanium dioxide can monitor excessive grinding of the inorganic coating layer by air powder, further improving the stability of titanium dioxide product quality and weather resistance. Summary of the Invention
[0004] The purpose of this invention is to provide a method for calculating the particle size and inorganic coating thickness of finished titanium dioxide products in order to overcome the shortcomings of the prior art.
[0005] The objective of this invention is achieved through the following technical solution:
[0006] A method for calculating the particle size and inorganic coating thickness of finished titanium dioxide product, assuming that the inorganic coating material and titanium dioxide particles are spherical, and assuming that the inorganic coating material is uniformly coated on the titanium dioxide particles; obtaining the density ρ of uncoated titanium dioxide after sand milling, and the ratio of the molecular molar mass of hydroxides or hydrates to oxides corresponding to different inorganic coating materials ω1, ω2, ..., ω... n The densities ρ1, ρ2, ..., ρ of different inorganic coating materials n The diameter d of uncoated titanium dioxide particles after sand milling was measured, and the percentage by mass of different inorganic coating materials in the finished titanium dioxide product was measured as x1, x2, ..., x. n Calculate the particle size D and coating thickness n of the finished titanium dioxide product using the following formulas, both in μm:
[0007]
[0008]
[0009] in:
[0010] d is the diameter D50 of the uncoated titanium dioxide particles after sand milling, in μm;
[0011] ρ represents the density of uncoated titanium dioxide after sand milling, in g / cm³. 3 ;
[0012] x1, x2, ..., x n The figures represent the mass percentage of different inorganic coating substances in the finished titanium dioxide product, expressed as %, and the mass fraction of TiO2 in the titanium dioxide, expressed as oxides, as x. TiO2 x TiO2 +x1+x2+……+x n =100%;
[0013] ω1, ω2, ..., ω n These are the ratios of the molecular molar mass of hydroxides or hydrates to oxides corresponding to different inorganic coating substances; if there are no hydroxides or hydrates, the ratio is 1 when calculated as oxides.
[0014] ρ1, ρ2, ..., ρ nThe values represent the densities of different inorganic coating substances, expressed as hydroxides or hydrates; for those without hydroxides or hydrates, they are expressed as oxides. The units are g / cm³. 3 .
[0015] Preferably, d is measured using a particle size analyzer, where d is the diameter D50 of the uncoated titanium dioxide particles after sand milling, in μm.
[0016] Preferably, XRF testing is used to determine the percentage of coating mass of different inorganic coating materials in the finished titanium dioxide product.
[0017] Preferably, the titanium dioxide is titanium dioxide produced by the sulfuric acid process or the chloride process after inorganic coating.
[0018] Preferably, the titanium dioxide has a crystal form of rutile, anatase, or mixed crystal.
[0019] Preferably, the inorganic coating material is selected from one or more combinations of the following substances:
[0020] Aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, phosphorus pentoxide, boron oxide, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, molybdenum oxide, tin oxide, antimony oxide, calcium oxide, tungsten oxide.
[0021] Preferably, when the titanium dioxide is uncoated anatase titanium dioxide, the mass percentage of anatase crystals is >90%, and the density of the titanium dioxide is 3.8–3.9 g / cm³. 3 ;
[0022] When the titanium dioxide is an uncoated mixed-crystalline titanium dioxide, the mass percentage of anatase is ≤90%, the mass percentage of rutile is ≤90%, and the density of the titanium dioxide is 4.0~4.1g / cm³. 3 ;
[0023] When the titanium dioxide is uncoated rutile titanium dioxide, the mass percentage of rutile crystals is >90%, and the density of the titanium dioxide is 4.2–4.3 g / cm³. 3 .
[0024] Preferably, when titanium dioxide is treated with an organic surface treatment agent, the mass percentage of the organic surface treatment agent added is ≤1%.
[0025] This application also provides a method for determining whether the finished titanium dioxide powder is over-ground. The particle size D50 of the finished titanium dioxide is tested using a particle size analyzer and compared with the particle size of the finished titanium dioxide calculated by the above-mentioned calculation method. If the particle size of the finished titanium dioxide tested by the particle size analyzer is smaller than the calculated particle size of the finished titanium dioxide, then the powder is determined to be over-ground.
[0026] This invention assumes that the inorganic coating material and titanium dioxide molecules are spherical, and that the inorganic coating material is uniformly coated onto the titanium dioxide particles. Then, by testing the particle size and density of the titanium dioxide particles before and after sand milling, the coating mass percentage of different inorganic coating materials in the finished product, the ratio of the molar molecular mass of the corresponding hydroxides or hydrates to oxides of different inorganic coating materials, and the density of the hydroxides or hydrates of different inorganic coating materials (or oxides if there are no hydroxides or hydrates), the inorganic coating thickness of the finished titanium dioxide products with different inorganic coatings can be calculated. This testing method avoids the problem of inaccurate particle size of coated titanium dioxide or finished product caused by agglomeration of titanium dioxide. It uses the volume of titanium dioxide obtained from the particle size of uncoated titanium dioxide after sand milling and the volume of coating material obtained through precise calculation, so as to accurately calculate the particle size of coated titanium dioxide, and then accurately calculate the coating thickness of titanium dioxide. The testing or calculation process is relatively simple, with a small amount of computation, and the data accuracy has been verified to be high. Compared with transmission electron microscopy, the calculation cost is lower and it is more suitable for titanium dioxide companies. Attached Figure Description
[0027] Figure 1 This is a transmission electron microscope image of the coated titanium dioxide provided in Example 1;
[0028] Figure 2 This is a transmission electron microscope image of the coated titanium dioxide provided in Example 2;
[0029] Figure 3 This is a transmission electron microscope image of the coated titanium dioxide provided in Example 3;
[0030] Figure 4 This is a transmission electron microscope image of the coated titanium dioxide provided in Example 4. Detailed Implementation
[0031] When titanium dioxide is treated with inorganic coating materials, the ideal coating state is that the inorganic coating material is uniformly deposited layer by layer on the outer surface of the titanium dioxide. Therefore, the coating thickness can theoretically be obtained by subtracting the uncoated titanium dioxide radius from the radius of the coated titanium dioxide or the radius of the finished titanium dioxide product (in the existing technology, organic surface treatment agents are sometimes added during the powder coating process, but the amount of organic coating agents added is small and can be ignored). However, as mentioned earlier, if the particle size of the coated titanium dioxide or the finished titanium dioxide product is simply measured using a particle size analyzer, the measured particle size is generally that of multiple agglomerates, and the test results have a large error. While transmission electron microscopy (TEM) offers higher accuracy, TEM is expensive and not applicable to production.
[0032] Based on the above, this invention provides a method for calculating the particle size and inorganic coating thickness of finished titanium dioxide. It assumes that the inorganic coating material and titanium dioxide particles are spherical, and that the inorganic coating material is uniformly coated onto the titanium dioxide particles. The method obtains the density ρ of uncoated titanium dioxide after sand milling, and the ratios ω1, ω2, ..., ωc of the molecular molar mass of hydroxides or hydrates to oxides corresponding to different inorganic coating materials. n The densities ρ1, ρ2, ..., ρ of different inorganic coating materials n The diameter d of uncoated titanium dioxide particles after sand milling was measured, and the percentage by mass of different inorganic coating materials in the finished titanium dioxide product was measured as x1, x2, ..., x. n Calculate the particle size D and coating thickness n of the finished titanium dioxide product using the following formulas, both in μm:
[0033]
[0034]
[0035] in:
[0036] d is the diameter D50 of the uncoated titanium dioxide particles after sand milling, in μm;
[0037] ρ represents the density of uncoated titanium dioxide after sand milling, in g / cm³. 3 ;
[0038] x1, x2, ..., x n The figures represent the mass percentage of different inorganic coating substances in the finished titanium dioxide product, expressed in %. As an oxide, the mass fraction of titanium dioxide is x. TiO2 , where x TiO2 +x1+x2+……+x n =100%;
[0039] ω1, ω2, ..., ω n These are the ratios of the molecular molar mass of the corresponding hydroxide or hydrate to the oxide for different inorganic coating materials; if there is no hydroxide or hydrate, the ratio is 1, calculated as oxide, such as phosphorus coating.
[0040] ρ1, ρ2, ..., ρ n The values represent the densities of different inorganic coating substances, calculated as hydroxides or hydrates; if no hydroxides or hydrates are available, they are calculated as oxides. The unit is g / cm³. 3 .
[0041] The above calculation formula is obtained through the following steps:
[0042] Step 1. Test the diameter D50 of the uncoated titanium dioxide particles after sand milling and record it as d (unit: μm). Calculate the volume V1 (unit: cm) of one uncoated titanium dioxide particle after sand milling. 3 The calculation formula is:
[0043]
[0044] Titanium dioxide particles that are not coated after sand milling should be thoroughly ground; the diameter D50 of titanium dioxide particles is preferably tested using a particle size analyzer, and more preferably a laser particle size analyzer.
[0045] Step 2. The density of the uncoated titanium dioxide after sand milling is ρ (unit: g / cm³). 3 The formula for calculating the mass (recorded as m, in g) of a single titanium dioxide particle after sand milling and without coating is as follows:
[0046]
[0047] The density ρ of titanium dioxide can be selected as 3.8 g / cm³. 3 3.9g / cm 3 4.0g / cm 3 4.1g / cm 3 Or 4.2g / cm 3 This depends on the type of titanium dioxide. Specifically, uncoated anatase titanium dioxide (with anatase crystal content > 90%) has a density of 3.8–3.9 g / cm³. 3 Uncoated mixed-crystal titanium dioxide (with anatase ≤90% and rutile ≤90% by mass) has a content of 4.0–4.1 g / cm³. 3 Uncoated rutile titanium dioxide (with a rutile crystal mass percentage >90%) has a content of 4.2–4.3 g / cm³. 3 .
[0048] Step 3. Test the different inorganic coating substances and their percentage mass ratios (all expressed as oxides) of the finished titanium dioxide product (after inorganic coating and gas powder processing), and record them as C1.
[0049] C2, ..., C n and x1, x2, ..., x n The mass fraction of TiO2 in titanium dioxide is x TiO2 x TiO2 +x1+x2+……+x n =100%; among which, XRF (X-ray fluorescence spectrometry) is preferred for testing; XRF is a conventional elemental analysis method that can directly obtain the types and contents of elements, and its cost is relatively lower than that of transmission electron microscopy, making it suitable for large-scale production.
[0050] Step 4. Calculate the volume V2 (in cm³) of the inorganic coating material of one titanium dioxide particle (calculated as hydroxide, or oxide or hydrate if no hydroxide is available). 3 The calculation formula is:
[0051]
[0052] in:
[0053] ω1, ω2, ..., ω n These are the ratios of the molecular molar mass of the corresponding hydroxides or hydrates to the oxides of different inorganic coating substances;
[0054] In existing technologies, the elemental content obtained through testing is generally the oxide content of the element. However, inorganic coating materials such as aluminum oxide and magnesium oxide coatings are actually deposited on the surface of titanium dioxide in the form of aluminum hydroxide and magnesium hydroxide hydroxides, while silicon dioxide and titanium dioxide are deposited in the form of hydrates. Therefore, the coating volume of inorganic coating materials in this step needs to be converted to hydroxide or hydrate calculations, specifically based on the actual deposition form of the inorganic coating material.
[0055] ρ1, ρ2, ..., ρ n The values represent the densities of different inorganic coating materials (calculated as hydroxides or hydrates; if no hydroxides or hydrates are available, they are calculated as oxides), in g / cm³. 3 ;
[0056] Step 5. Calculate the particle size D and coating thickness n of a single finished titanium dioxide particle, both in μm. The calculation formula is:
[0057]
[0058]
[0059] in:
[0060] d represents the diameter of the uncoated titanium dioxide particles after sand milling, in μm.
[0061] ρ represents the density of uncoated titanium dioxide after sand milling, in g / cm³. 3 ;
[0062] x1, x2, ..., x n The figures represent the mass percentage of different inorganic coating substances in the finished titanium dioxide product, in % (%). The mass fraction of TiO2 in the titanium dioxide, expressed as oxides, is x. TiO2 x TiO2 +x1+x2+……+x n =100%;
[0063] ω1, ω2, ..., ω n These are the ratios of the molecular molar mass of the corresponding hydroxides or hydrates to the oxides of different inorganic coating substances;
[0064] ρ1, ρ2, ..., ρ n The density of different inorganic coating materials is given (calculated as hydroxide or hydrate, or as oxide if no hydroxide or hydrate exists, mainly involving phosphorus pentoxide), in g / cm³. 3 .
[0065] Preferably, the titanium dioxide is inorganically coated titanium dioxide produced by the sulfuric acid or chloride process. It can be rutile titanium dioxide (rutile crystal content > 90%), anatase titanium dioxide (anatase crystal content > 90%), or mixed-crystal titanium dioxide (anatase crystal content ≤ 90%, rutile crystal content ≤ 90%). The titanium dioxide can also be treated with an organic surface treatment agent during the gasification process. To avoid excessive organic coating affecting test results, the amount of organic surface treatment agent used should be ≤ 1% by mass.
[0066] Preferably, the inorganic coating material can be one or more of the following: aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, phosphorus pentoxide, boron oxide, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, molybdenum oxide, tin oxide, antimony oxide, calcium oxide, and tungsten oxide.
[0067] This invention assumes that the inorganic coating material and titanium dioxide molecules are spherical, and that the inorganic coating material is uniformly coated onto the titanium dioxide particles. Then, by testing the particle size and density of the titanium dioxide particles after sand milling before coating, the coating mass percentage of different inorganic coating materials in the finished product, the ratio of the molar molecular mass of the corresponding hydroxides or hydrates to oxides of different inorganic coating materials, and the density of hydroxides or hydrates of different inorganic coating materials, the particle size and inorganic coating thickness of the finished titanium dioxide products with different inorganic coatings can be calculated. This testing method avoids the problem of inaccurate particle size of coated titanium dioxide or finished titanium dioxide products caused by agglomeration. It uses the more accurate volume of uncoated titanium dioxide obtained from the particle size after sand milling and the precisely calculated volume of the coating material to accurately calculate the particle size of the coated titanium dioxide, and thus accurately calculate the coating thickness. The testing or calculation process is relatively simple, with low computational load, and the verified data accuracy is high. Compared with transmission electron microscopy, the calculation cost is lower, making it more suitable for titanium dioxide companies. By monitoring the coating thickness of titanium dioxide, production can be theoretically guided, ensuring that titanium dioxide has a more suitable particle size for downstream applications, thereby achieving better pigment performance. Simultaneously, by calculating the accurate particle size of the coated titanium dioxide, the particle size of the finished titanium dioxide product can be monitored during production, avoiding film peeling caused by excessive powder vaporization, further improving the stability of titanium dioxide product quality and weather resistance. Specifically, the particle size D50 of the finished titanium dioxide product is tested using a particle size analyzer and compared with the particle size of the finished titanium dioxide product calculated by the above calculation method. If the particle size of the finished titanium dioxide product tested by the particle size analyzer is smaller than the calculated particle size of the finished titanium dioxide product, it is determined that the gas powder is over-ground, and there is a risk of film layer peeling off, which will affect the weather resistance and other application performance of the titanium dioxide.
[0068] Example 1
[0069] Before inorganic coating treatment, the particle size d of uncoated rutile titanium dioxide after sand milling was 0.310 μm, and the density ρ was 4.2 g / cm³. 3 Then, after inorganic coating, water washing, flash drying, and vapor powder treatment, titanium dioxide product 1 was obtained. XRF testing showed that the coating material of titanium dioxide product 1 was aluminum oxide, with a content (x1) of 4.0%. The molar mass ratio (ω1) of aluminum hydroxide to aluminum oxide was 1.53, and the density (ρ1) of aluminum hydroxide was 2.42 g / cm³. 3 Therefore, according to the above calculation formula, the finished particle size D of titanium dioxide 1 is calculated to be 0.321 μm, and the coating thickness n is 0.00552 μm.
[0070] Example 2
[0071] Before inorganic coating treatment, the particle size d of uncoated rutile titanium dioxide after sand milling was tested to be 0.332 μm, and the density ρ was 4.3 g / cm³.3 Then, after inorganic coating, water washing, flash drying, and steam drying, titanium dioxide product 2 was obtained. XRF testing showed that the coating material of titanium dioxide product 2 was alumina and zirconium oxide, with contents x1 and x2 of 2.5% and 0.4%, respectively. The molar mass ratios ω1 and ω2 of aluminum hydroxide to alumina and zirconium hydroxide to zirconium oxide were 1.53 and 1.29, respectively. The densities ρ1 and ρ2 of aluminum hydroxide and zirconium hydroxide were 2.42 g / cm³. 3 and 3.25g / cm 3 Therefore, according to the above calculation formula, the finished particle size D of titanium dioxide 2 is 0.340 μm and the coating thickness n is 0.00416 μm.
[0072] Example 3
[0073] Before inorganic coating treatment, the particle size d of uncoated rutile titanium dioxide after sand milling was 0.326 μm, and the density ρ was 4.3 g / cm³. 3 Then, after inorganic coating, water washing, flash drying, and vaporization, titanium dioxide 3 was obtained. XRF testing showed that the coating material of titanium dioxide 3 was alumina and silicon dioxide, with contents x1 and x2 of 1.5% and 2.7%, respectively. The molar mass ratios ω1 and ω2 of aluminum hydroxide to alumina, silica gel, and silicon dioxide were 1.53 and 1.30, respectively. The densities ρ1 and ρ2 of aluminum hydroxide and dense silica gel were 2.42 g / cm³. 3 and 1.60 g / cm 3 Therefore, according to the above calculation formula, the finished particle size D of titanium dioxide 3 is 0.341 μm and the coating thickness n is 0.00733 μm.
[0074] Example 4
[0075] Before inorganic coating treatment, the particle size d of uncoated rutile titanium dioxide particles after sand milling was measured to be 0.353 μm, and the density ρ was 4.2 g / cm³. 3 Then, after inorganic coating, water washing, flash drying, and steam drying, titanium dioxide 4 was obtained as the finished product. XRF testing showed that the coating material of titanium dioxide 4 was aluminum oxide and phosphorus pentoxide, with contents of 4.5% and 3.1% (x1 and x2), respectively. The molar mass ratio of aluminum hydroxide to aluminum oxide (ω1) was 1.53, and that of phosphorus pentoxide (ω2) was 1.00. The densities of aluminum hydroxide and phosphorus pentoxide (ρ1 and ρ2) were 2.42 g / cm³, respectively. 3 and 2.39 g / cm 3 Therefore, according to the above calculation formula, the finished particle size D of titanium dioxide 4 is 0.374 μm and the coating thickness n is 0.01045 μm.
[0076] The coating thickness of titanium dioxide products 1, 2, 3, and 4 was tested using TEM. The test results are as follows: Figures 1-4 As shown in Tables 1 and 2.
[0077] Table 1. Results of transmission electron microscopy (TEM) test on the thickness of the inorganic coating of titanium dioxide.
[0078]
[0079] Table 2 Comparison of Test Results for Inorganic Coating Thickness of Titanium Dioxide
[0080]
[0081] From the above embodiments, Figures 1-4 As shown in Tables 1 and 2, the calculation method used in this invention is simple, easy to implement, and requires little computation. Compared to the 10nm error of a general particle size analyzer, the error is ≤1nm, resulting in more accurate results. Compared to transmission electron microscopy, the test results are comparable, and the calculation cost is lower, making it more suitable for titanium dioxide enterprises. By monitoring the coating thickness of titanium dioxide, production can be theoretically guided, ensuring that titanium dioxide has a more suitable particle size in downstream applications, thereby achieving better pigment performance. At the same time, by calculating the accurate particle size of the coated titanium dioxide, the finished particle size of the titanium dioxide in production can be monitored, avoiding the problem of film peeling caused by excessive grinding (if the finished particle size of titanium dioxide tested by the particle size analyzer is smaller than the calculated particle size of the coated titanium dioxide, then excessive grinding by grinding will cause the film to peel off, affecting the weather resistance and other application performance of titanium dioxide), further improving the stability of titanium dioxide product quality and weather resistance.
[0082] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention. Clearly, those skilled in the art can make various alterations and modifications to the invention without departing from its spirit and scope. Thus, if these modifications and modifications of the invention fall within the scope of the claims and their equivalents, the invention is also intended to include these modifications and modifications.
Claims
1. A method for calculating the particle size and inorganic coating thickness of finished titanium dioxide, characterized in that, Assuming the inorganic coating material and titanium dioxide particles are spherical, and that the inorganic coating material uniformly coats the titanium dioxide particles; obtain the density ρ of the uncoated titanium dioxide after sand milling, and the ratios ω1, ω2, ..., ωc of the molecular molar mass of hydroxides or hydrates to oxides corresponding to different inorganic coating materials. n The densities ρ1, ρ2, ..., ρ of different inorganic coating materials n The diameter d of uncoated titanium dioxide particles after sand milling was measured, and the percentage of coating mass of different inorganic coating materials in the finished titanium dioxide product was measured as x1, x2, ..., x. n Calculate the particle size D and coating thickness n of the finished titanium dioxide product using the following formulas, where both units are in μm: in: d is the diameter D50 of the uncoated titanium dioxide particles after sand milling, in μm; ρ represents the density of uncoated titanium dioxide after sand milling, in g / cm³. 3 ; x1, x2, ..., x n The figures represent the mass percentage of different inorganic coating substances in the finished titanium dioxide product, expressed as %, and the mass fraction of TiO2 in the titanium dioxide, calculated as oxides, is x. TiO2 x TiO2 +x1+x2+……+x n =100%; ω1, ω2, ..., ω n These represent the ratio of the molecular molar mass of the hydroxide or hydrate to the oxide corresponding to different inorganic coating substances; if there is no hydroxide or hydrate, the ratio is 1 when the oxide is used. ρ1, ρ2, ..., ρ n The values represent the densities of different inorganic coating substances, expressed as hydroxides or hydrates; for those without hydroxides or hydrates, they are expressed as oxides. The units are g / cm³. 3 .
2. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 1, characterized in that, The particle size distribution d was measured using a particle size analyzer. d is the diameter D50 of the uncoated titanium dioxide particles after sand milling, and the unit is μm.
3. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 1, characterized in that, XRF was used to test the coating mass percentage of different inorganic coating materials in the finished titanium dioxide product.
4. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 1, characterized in that, The titanium dioxide is titanium dioxide produced by the sulfuric acid process or the chloride process and has undergone inorganic coating.
5. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 1, characterized in that, The titanium dioxide has one of the following crystal forms: rutile, anatase, or mixed crystal.
6. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 1, characterized in that, The inorganic coating material is selected from one or more combinations of the following substances: Aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, phosphorus pentoxide, boron oxide, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, molybdenum oxide, tin oxide, antimony oxide, calcium oxide, tungsten oxide.
7. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 5, characterized in that, When the titanium dioxide is uncoated anatase titanium dioxide, the mass percentage of anatase crystals is >90%, and the density of the titanium dioxide is 3.8–3.9 g / cm³. 3 ; When the titanium dioxide is an uncoated mixed-crystalline titanium dioxide, the anatase crystal mass percentage is ≤90%, the rutile crystal mass percentage is ≤90%, and the density of the titanium dioxide is 4.0~4.1g / cm³. 3 ; When the titanium dioxide is uncoated rutile titanium dioxide, the mass percentage of rutile crystals is >90%, and the density of the titanium dioxide is 4.2–4.3 g / cm³. 3 .
8. The method for calculating the particle size and inorganic coating thickness of finished titanium dioxide as described in claim 1, characterized in that, When titanium dioxide is treated with an organic surface treatment agent, the mass percentage of the organic surface treatment agent added shall be ≤1%.
9. A method for determining whether finished titanium dioxide powder has been over-ground, characterized in that, The particle size D50 of the finished titanium dioxide product is tested using a particle size analyzer and compared with the particle size of the finished titanium dioxide product calculated by the calculation method described in any one of claims 1 to 8. If the particle size of the finished titanium dioxide product tested by the particle size analyzer is smaller than the calculated particle size of the finished titanium dioxide product, it is determined that the gas powder has been over-ground.
Citation Information
Patent Citations
Quick measuring method of grain size of titanium pigment
CN107976385A
Method for rapidly testing and calculating concentration of titanium dioxide slurry
CN113218804A